تطور المؤشرات الكمية لقياس الاثار الاقتصادية للأنفاق العام ومعدلات النمو للاقتصاد الليبي خلال الفترة ( 1986 - 2017 ) (Economic studies journal, 2020)
This study aims to analyze the development of quantitative indicators to measure the economic effects of public expenditure on the economic growth in Libya during the time period from 1986 to 2017. A great concentration is made on most important variables that reflect the quantitative indicators to examine the economic effects of public expenditure. In regard of methodology, the study consists of two parts. the first part contains using an analytical method to display the chronological development of public expenditure (consumer and investment spending), whilst, the second part comprises employing Autoregressive Distributed Lag Model (ARDL) to determinate the effect of public expenditure on the economic growth during the same period. The results reveal that the great size of the public expenditure goes to the consumer spending, while the investment spending gets the Less share. Moreover, the results of the ARDL model show that there is a positive relationship between the public expenditure and the economic growth in the long and short-run. Therefore, the study recommends to implement substantial procedures such as rationalizing public expenditure and Differentiating between them at the expense of their effectiveness.